Evaluasi Pelaksanaan Pekerjaan Lapis Fondasi Agregat Semen Kelas A (CTB) - Hajo, Dody Suraya (Jurnal Teknologi Berkelanjutan, 2025)
In road construction projects in Kapuas Regency, differences in UCS (Uniaxial Compressive Strength) values are often found between CTB samples that remain in the cylindrical molds and those that have been removed, even though they originate from the same mixture. A similar case occurred in the Kapuas–Mandomai project in 2024, where there was a significant discrepancy in UCS values. This paper aims to share experiences regarding CTB compressive strength testing results and emphasize the importance of evaluating the factors contributing to UCS reduction as a consideration for future projects.CTB work in this area is typically carried out after the spreading and compaction of Aggregate A with a width of 5.5 meters and a thickness of 30 cm, as planned. Next, cement is spread on the road surface at a 5% content based on the job mix design and offer analysis, then mixed using a recycling machine and water tanker moving simultaneously until a homogeneous mixture is achieved. The water tanker functions to add the required moisture content. After mixing, the material is shaped and compacted.For laboratory testing, five cylindrical samples were taken—three tested on the first day and two on the second day. The results showed UCS values of 38.09 kg/cm² and 45.25 kg/cm², respectively. This variation is suspected to be caused by uneven cement distribution and sample disturbance when removed from the mold. The use of a cement spreader is recommended for more uniform cement distribution, along with matching the number of samples with the available molds. Further research is needed to gain deeper insight into the causes of CTB quality reduction in the field.